Cost reduction workshops - Hazlina, Faizal (Penerbit UMP, 2013)
Two series of workshop on cost-cutting measures were conducted on December 15-16, 2012 and January 12-13, 2013 with the main objective was to identify prudent practices in managing expenses at all of Universiti Malaysia Pahang (UMP)'s Responsibility Centres (RCs).